Study On Processing Parameters For Polypropylene Reinforced With Fiber Glass Composite Prepared Using Injection Molding - Rusli, Nur Syamimi (2019)
This report reveals the effect of processing parameters on mechanical properties for palypropylene reinforced with fiber glass composite prepared by injection molding process. The processing parameters involved on the experimental are melting temperature (MeT) (250°C — 280°C, injection pressure (IP) (22 MPa — 28 MPa) and cooling time (Ct) (60s — 90s). Box Behnken response surface method (RSM) was used to determine the most influential paremeters affected the experimental responses that are tensile strength, modulus strength and percentage of elongation. Further, investigation the optimum processing parameters value that give hi highest tensile strength, highest tensile modulus and shortest elongation were studied. There were 17 numbers of experimental run with three repetitions was conducted using the injection molding machine. The result collected was optimized using RSM meanwhile the analysis of variance (ANOVA was used to calculated the P-value and R-squared to find the most significant parameter affected the response. From the result analysis,it is found that the injection pressure is the most significant parameter that affacted tensile strength and percentage of elongation. Meanwhile, melting temperature shows the most significant parameter affected on the tensile modulus. The optimum parameters affected the tensile strength are 250°C for MeT, 22 MPa for IP and 77.97s for Ct Further, optimum parameters affected the tensile modulus are 262.4°C for MeT, 27.0 MPa for IP and 60s for Ct. Finally, optimum parameters affected the percentage o elongation are 250°C for MeT, 28 MPa for IP and 90s for Ct. The multi optimization shows that the multiple optimized parameters valuesare 252.4°C for MeT, 27, 8 MPa for IP and 60s for Ct which resulted the responses of tensile strength, modulus strength and percentage of elongation are 18.99 MPa, 2092.53 MPa and 12.31% respectively. Thus, RSM and ANOVA analysis can be used to optimized the injection moulding machine parameters that affected the mechanical properties of polypropylene reinforced with fiber glass composite.